Conocimiento y acciones de autocuidado del adulto mayor Hospital Leoncio Prado Huamachuco - Polo Briceño, Adriana Olinda (2019)
The present investigation of descriptive correlational type was carried out in order to determine the relationship between the level of knowledge and the self-care actions of the elderly of the Senior Adult Program of the Hospital Leoncio Prado Huamachuco, the sample population consisted of 25 older adults of the Older Adult Program that fulfilled the established inclusion criteria to whom two questionnaire-type instruments on knowledge level and self-care actions were applied, using the chi-squared test to analyze the statistics, reaching the following conclusions: 72.0 percent they refer a good level of knowledge about self-care actions and only 28.0 percent have a poor level of knowledge. 84.0 percent of older adults report enhancing self-care actions and only 16.0 percent bad actions. There is a significant relationship between the level of knowledge and the self-care actions of the older adult p <0.001.